Aggregation‐induced emission active 3, 6‐bis(1, 2, 2‐triphenylvinyl)carbazole and bis(4‐(1, 2, 2‐triphenylvinyl)phenyl)amine‐based poly(acrylates) for explosive detection. Issue 4 (12th October 2016) - Chua, Ming Hui; Zhou, Hui; Lin, Ting Ting; Wu, Jishan; Xu, Jian Wei
ABSTRACT: Four novel aggregation‐induced emission (AIE)‐active poly(acrylates), in which AIE‐active luminogens 3, 6‐bis(1, 2, 2‐triphenylvinyl)carbazole (BTPC) and bis(4‐(1, 2, 2‐triphenylvinyl)phenyl)amine (BTPPA) were linked to the polymer backbone via a flexible alkyl chain, were synthesized in high yields. Spectrofluorometric analysis of polymer nano‐aggregates in tetrahydrofuran/water revealed that PTPPA‐based polymers gave more sensitive fluorescence response to nitro‐aromatics including 2, 4, 6‐trinitrotoluene than BTPC‐based polymers. Paper probes were also fabricated for solid‐state detection of explosives. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 672–681 Abstract : This article reports the synthesis of aggregation‐induced emission (AIE) active poly(acrylates) comprising two new AIE luminogens. Four polymers exhibit fluorescence quenching response to nitro‐aromatic compounds. The paper sensors are fabricated by coating polymer nanoparticle suspensions onto a piece of filter paper, showing obvious fluorescence quenching response to explosives and hence endowing a useful tool to detect explosives in a fast and cheap way.